THE EMBLEMATIC FOOD OF QUARTA COLÔNIA AS A MENS OF CULTURAL AND SOCIAL INTERACTION - FRIGO, MARINA SACILOTO FRIGO (2023)
Preserving the gastronomic culture of a territory is essential to keep alive their identity, in addition to safeguarding traditions that passed down from generation to generation. This territorial identity, manifested through culinary habits, memories and traditional know-how linked to food, is what is perceived in Quarta Colônia, located in the central region of Rio Grande do Sul. Its emblematic food is mainly the result of the influences of European immigrants who colonized the territory in the 19th century, being valued and demanded by tourists looking for food authenticity. Through a qualitative approach, using the narrative analysis method and secondary and primary data, the objective is to identify these foods, recall, disseminate and provide material for the promotion of the culture of the Quarta Colônia territory, to contribute to its development and safeguarding its assets.